Amplification of the fusion gene of rinderpest virus by polymerase chain reaction and cloning in bacteria - Bulut, H; Doymaz, MZ; Bolat, Y (Scientific Technical Research Council Turkey, 2001)
In this study, amplification of the rinderpest virus (RPV) fusion (F) gene with polymerase chain reaction (PCR) and cloning of the F gene in Escherichia coli were reported. For this purpose, first total mRNA from Vero cells infected with Vaccine strain of RPV was obtained and then cDNA from this mRNA preparation was acquired with reverse transcription. In PCR, cDNA from infected Vero cells and F gene specific primers were used and the F gene was amplified. Both the PCR product and the cloning vector pUC19 were cut with EcoRI and HindIII restriction enzymes. By using T4 DNA ligase, insert and vector were ligated. The resulting recombinant plasmid was used in the transformation of DH5 proportional to competent E. coli cells. The transformed cells were inoculated onto Lurie-Bertani (IB) agar plates containing ampicillin. The presence of the RPV-F gene in the recombinant plasmid pUCF was confirmed with both the PCR and restriction enzyme digestion assays.
Si?ir Vebasi Virüsünün Füzyon Geninin Polimeraz Zincir Tepkimesiyle Ço?altilmasi ve Bakteriyel Klonlanmasi
Keywords: rinderpest virus; fusion gene; cloning